Photocatalytic oxidation of gas phase volatile organic compounds using undoped and metal ions doped titanium dioxide thin films - 253984 Noor Khaida Wati Mohd. Saiyudi (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2006